Redécouverte d’un milliaire romain. La borne de Chaspuzac (Haute-Loire), cité des Vellaves (province d’Aquitaine) - Marion Dacko (Revue Archéologique du Centre de la France)
The research started as part of a thesis on Roman roads in the Arverne and Vellave territory has recently led to the rediscovery of a milestone, lost in the storerooms of the Crozatier museum at Puy-en-Velay (Haute-Loire) since the end of the 19th century. A thorough reexamination of the inscription has enabled a revision of previous writings in the light of new information. An addition to the series of milestones of the Emperor Maximinus, this stone is evidence of the great repair works undertaken on the Bolène Way throughout the 3rd century.